MENGGALI EFEKTIVITAS PODCAST ‘LOGIN’ SEBAGAI MEDIA MEMBANGUN TOLERANSI ANTARAGAMA DI INDONESIA - Yunita, Niken; Jenuri (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Indonesia, which is rich in cultural and religious diversity, makes religious tolerance an important pillar to strengthen national unity. This diversity is not only reflected in people's daily lives, but is also an interesting topic that can be explored through various media, including digital media. This research is qualitative research that takes concrete examples from Deddy Corbuzier's YouTube channel, especially the LogIn podcast, as a means of understanding how religious tolerance is manifested in the content presented to the public. The aim of this research is to analyze the effectiveness of the LogIn podcast in promoting and strengthening interreligious tolerance in Indonesia. The focus of this research is on content analysis, audience response and interaction, as well as the social impact produced by podcasts in the context of religious diversity in Indonesia. The research results show that presenting LogIn content with an inclusive da'wah approach and inter-religious dialogue is effective in reducing racism and intolerance. This inclusive da'wah refers to efforts to open a space for discussion that respects the views of various religions without prioritizing one particular party. This initiative supports the formation of a more harmonious society and respects the principle of Bhinneka Tunggal Ika, which is the foundation of harmony in Indonesia.